A Versatile Approach for the Assembly of Highly Tunable Biocatalytic Thin Films. Issue 18 (24th July 2019) - Rodriguez‐Abetxuko, Andoni; Sánchez‐deAlcázar, Daniel; Cortajarena, Aitziber L.; Beloqui, Ana
Abstract: The deposition of protein thin films on (in)organic surfaces is a key approach to incorporate new functionalities into these materials for a broad number of applications. However, most of the current methods used for the controlled assembly of such biomolecules and eventual film formation are limiting since entail either the chemical modification of the proteins, which leads sometimes to impaired materials, or the sequential layer‐by‐layer deposition of charged macromolecules. In this work, a facile bioinspired method for the versatile fabrication of robust catalytic films is developed. The herein shown approach involves the one‐pot synthesis of porous enzyme nanogels decorated with imidazole motifs. These nanogels act as small nanoreactors that are further self‐assembled into continuous catalytic nanocoatings through metal‐imidazole coordination. An extensive structural, chemical, and functional characterization of the biocatalytic coatings evidences the integrity, stability in organic solvents and high temperatures, and the reusability of the deposits. Moreover, the thickness and metal composition of the nanocoatings can be tuned on demand. Finally, interesting applications for the bioinspired films are demonstrated, i.e., the fabrication of a glucose electrochemical biosensor and the completion of tandem enzymatic reactions, which suggest a broad applicability potential of this methodology. Abstract : Metal‐imidazole coordination is herein used as driving force for the supramolecular assembly of enzyme nanogels into robust and highly stable functional thin films. The utilization of these films in attractive technological applications is successfully explored, i.e., the fabrication of a glucose electrochemical biosensor and the colocalization of enzymes for tandem catalytic reactions.